Factors That Influence Perceived Organizational Support for Emotional Labor of Chinese Medical Personnel in Hubei - Zeng, Zhi; Wang, Xiaoyu; Bi, Haoran; Li, Yawen; Yue, Songhua; Gu, Simeng; Xiang, Gaoyue (Frontiers in Psychology, 2021)
At the outbreak of coronavirus disease in Wuhan, China, 42,322 medical personnel from other provinces and municipalities in China volunteered to rush to Hubei to assist their colleagues. Their all-out efforts contributed to Hubei finally winning the fight to prevent and control the pandemic. This study explores the influence of perceived organizational support on the emotional labor of medical personnel in Hubei Province. A group of 170 medical personnel were investigated using the perceived organizational support scale, emotional labor scale, and professional identity scale. The results show that a strong sense of organizational support can promote higher emotional labor among medical workers in Hubei Province. A strong sense of organizational support will also promote a stronger professional identity; further, a strong professional identity completely mediates the effect of perceived organizational support on emotional labor. These results infer that in emergency medical and health services, medical personnel can realize a high sense of organizational support, which could enhance their professional identity; this enables them to combine their professional goals with organizational goals more actively and to finally pay higher emotional labor to achieve organizational goals.